Ocimum Gratissimum: The Brine Shrimps Lethality of a New Chemotype Grown in South Western Nigeria (Global Journal of Science Frontier Research, 2012)
Hydro-distilled volatile oils of leaves and seeds of Ocimum gratissimum L. (Lamiaceae) were investigated for chemical constituents and brine shrimp lethality activity. The essential oil of the leaves of O. gratissimum consisted of Î³- terpinene (52.86%), Z-tert-butyl-4- hydroxy anisole (13.93%), caryophyllene (10.37%) and p-cymenene (7.16%) as the major compounds while the essential oils of the seeds yielded Î±- pinene (48.19%), caryophyllene (10.71%), and 3-tert-butyl-4- hydroxyanisole (11.14%) as the major compounds. The volatile oils showed significant toxicity against brine shrimps, Artemia salina, as 100% mortality was recorded at 1000 ppm for the different essential oils.
Keywords: Essential oil; Hydro-distillation; Ocimum gratissimum; Artemia salina; toxicity